Revisão sistemática da literatura sobre a efetividade clínica do plasma rico em plaquetas para o tratamento dermatológico estético - Donadussi, Márcia (2012)
Objective: To evaluate the evidence on the clinical efficacy of platelet-rich plasma (PRP) for aesthetic treatment of the skin. Material and Methods: a narrative review was conducted initially on skin aging, options for cosmetic treatment of the aged skin, growth factors from platelets and the use of platelet-rich plasma to tissue regeneration in the experimental setting. This was followed by a comprehensive systematic review of medical literature to evaluate the clinical efficacy of PRP in the aesthetic treatment of the skin, which aimed to answer the research question. The included databases were MEDLINE, Embase and Cochrane CENTRAL. Human clinical trials evaluating the effect of PRP as a dermal stimulator in the aesthetic treatment of the skin were included. Literature search, articles selection and data extraction were performed by two independent reviewers. Results: Only seven out of 2132 identified articles met the inclusion criteria of the systematic review. Of these, 5 evaluated the effect of application of PRP for facial skin and acne scars treatment, skin renewal, prominent nasolabial folds or as ajduvant for facial plastic surgery. Two other studies have evaluated histological changes resulting from the application of PRP in the skin of the arms. All evaluated studies have demonstrated beneficial result related to PRP application. However the studies had major limitations such as small sample size, non-uniform outcome evaluation criteria and lack of a control group. Conclusion: Current scientific evidence identified through systematic review suggests that PRP is a promising method for the cosmetic treatment of the skin. However, larger clinical studies are needed with better outcomes evaluation criteria to define the role of PRP in clinical practice.